The world of tomorrow : a novel - Mathews, Brendan (New York : Little, Brown and Company, 2017)
Fleeing Ireland for New York City after stealing a small fortune from the IRA, three brothers immerse themselves in the cultural and political tensions of 1939, only to find their lives falling apart when they are tracked down by a hired assassin.
Keywords: Brothers -- Fiction; Irish Americans -- New York (State) -- New York -- Fiction; Brothers -- Fiction; Irish Americans -- New York (N.Y.) -- Fiction; New York (N.Y.) -- History -- 1898-1951 -- Fiction; New York (N.Y.) -- History -- 20th century -- Fiction; Historical fiction; Historical fiction